With a little help from nuestros amigos : Hispanics and kidney transplants - Hennessy, Julie (London : SAGE Publications Ltd, 2017)
Dr. Juan Caicedo was educated in general medicine and surgery at Universidad Nacional de Colombia and practiced transplant medicine in Bogota. He determined that he would need to go to the United States to advance his training, and ultimately was awarded a fellowship in transplant surgery at Northwestern Memorial Hospital. During his three years as a fellow, Caicedo was struck by the number of Hispanic patients on the kidney transplant waiting list. Not only were Hispanics the highest growth group on the transplant waiting list, they also waited longer for transplants and died while waiting at higher rates than non-Hispanic whites or African-Americans. Caicedo also was alarmed by Hispanic patients lower utilization of living donors for transplantation they were underrepresented not only as live donor transplant patients, but also as donors. As he neared the end of his fellowship in 2006, Caicedo wondered if the Hispanic population encountered unique barriers to transplantation and living donor usage, and began to think about creating a program to address these barriers.
Originally published in Hennessy, J. (2016). With a little help from Nuestros Amigos: Hispanics and kidney transplants. 5-116-003. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Discrimination in medical care; Transplantation of organs, tissues, etc; Hispanic Americans -- Medical care